Influence of Culture Work and Motivation Achievement of the Creativity Employees Manado State University - Tangkau, Valentino; Bogar, Wilson; Kairupan, Sisca Beatrix (Technium Social Sciences Journal, 2021)
Research is carried out to know the influence of the culture of work and motivation to excel in partial and simultaneously to the creativity of employees Unima. The research uses a quantitative approach. The population is all Unima employees totaling 369 employees consisting of 88 structural officers and 281 implementers, spread on 14 units. Mechanical sampling was carried out in two stages. Namely, stage first performed with technique purposive sampling, i.e., selected or assigned only employee executive or employee who does not occupy the structural post. Employees structurally no longer included in determining the size of the sample stage of the second. The second stage is carried out by proportional random sampling, where the work unit sees the proportion at Unima. The size of the sample is calculated by the rules of Jalaluddin and obtained 75 employees. The data collection technique is a questionnaire that had been tested the validity and reliability. Analysis of the data is the analysis of regression doubled with the help of SPSS. Results of the study revealed that (1) the culture of work affects positively and significantly the creativity of employees Unima, (2) motivation to excel influences positively and significantly to the creativity of employees Unima, (3) the culture of work and motivation to work in the simultaneous influence positively and significantly to the creativity of employees Unima. Suggested for strengthening the culture of work, so should the value and norms that have been agreed together that have set attitudes and behaviors in work and interact in the work environment carried out consistently and sustainably. To increase the motivation of achievement, it should award and systems career to the promotion positions implemented in a transparent and consideration of performance.